Identification and characterization of more than 4 million intervarietal SNPs across the group 7 chromosomes of bread wheat. Issue 1 (22nd August 2014) - Lai, Kaitao; Lorenc, Michał T.; Lee, Hong Ching; Berkman, Paul J.; Bayer, Philipp Emanuel; Visendi, Paul; Ruperao, Pradeep; Fitzgerald, Timothy L.; Zander, Manuel; Chan, Chon‐Kit Kenneth; Manoli, Sahana; Stiller, Jiri; et al.
Summary Despite being a major international crop, our understanding of the wheat genome is relatively poor due to its large size and complexity. To gain a greater understanding of wheat genome diversity, we have identified single nucleotide polymorphisms between 16 Australian bread wheat varieties. Whole‐genome shotgun Illumina paired read sequence data were mapped to the draft assemblies of chromosomes 7A, 7B and 7D to identify more than 4 million intervarietal SNPs. SNP density varied between the three genomes, with much greater density observed on the A and B genomes than the D genome. This variation may be a result of substantial gene flow from the tetraploid Triticum turgidum, which possesses A and B genomes, during early co‐cultivation of tetraploid and hexaploid wheat. In addition, we examined SNP density variation along the chromosome syntenic builds and identified genes in low‐density regions which may have been selected during domestication and breeding. This study highlights the impact of evolution and breeding on the bread wheat genome and provides a substantial resource for trait association and crop improvement. All SNP data are publically available on a generic genome browser GBrowse at www.wheatgenome.info.